SOCIALLY RESPONSIBLE ACTIVITIES TO ENSURE QUALITY EDUCATION IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT - Бержанір, А. (Modern engineering and innovative technologies, 2024)
The article discusses the theoretical foundations of socially responsible activities to ensure quality education in the context of sustainable development. The necessity of systematic implementation of the social responsibility policy in interaction with